2015
DOI: 10.1111/jac.12125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cold Tolerance in NERICAs Compared with Japanese Standard Rice Varieties at the Reproductive Stage

Abstract: New Rice for Africa (NERICA) is a general name for interspecific rice varieties derived from a cross between the high-yielding Asian rice (Oryza sativa L.) between locally adapted African rice (Oryza glaberrima Steud.). Eight NERICAs were evaluated for cold tolerance (CT) at the reproductive stage and compared with their O. sativa parents and three Japanese standard rice varieties over 3 years. Cold tolerance was evaluated based on the filled grain ratio (FGR) after cold water irrigation. The FGR was greatly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
5
17
0
Order By: Relevance
“…Moreover, heavy panicle-type varieties with large sink size tend to have a higher proportion of pre-heading reserve assimilates in total carbohydrates in the panicles (Gendua et al, 2009;Kusutani et al, 1993;Miah et al, 1996;Saitoh et al, 1991;Song et al, 1990;Yamamoto, 1991). NERICA varieties are classified as panicle weight-type (Tsunematsu & Takagi, 2004) because of the higher number of spikelets per panicle and fewer panicles (Kikuta et al, 2017;Matsunami et al, 2009;Wainaina et al, 2015). Thus, morphological characteristics of the panicles might explain the higher proportion of pre-heading reserve assimilates in the total carbohydrate in the panicles of NERICAs (Table 3).…”
Section: Varietal Differencesmentioning
confidence: 99%
“…Moreover, heavy panicle-type varieties with large sink size tend to have a higher proportion of pre-heading reserve assimilates in total carbohydrates in the panicles (Gendua et al, 2009;Kusutani et al, 1993;Miah et al, 1996;Saitoh et al, 1991;Song et al, 1990;Yamamoto, 1991). NERICA varieties are classified as panicle weight-type (Tsunematsu & Takagi, 2004) because of the higher number of spikelets per panicle and fewer panicles (Kikuta et al, 2017;Matsunami et al, 2009;Wainaina et al, 2015). Thus, morphological characteristics of the panicles might explain the higher proportion of pre-heading reserve assimilates in the total carbohydrate in the panicles of NERICAs (Table 3).…”
Section: Varietal Differencesmentioning
confidence: 99%
“…There are currently 18 varieties suited for upland growth conditions (NERICA 1 to NERICA 18) (Wainaina et al, 2015). The use of these improved rice varieties is expected to achieve remarkable yield improvements (Kijima et al, 2006) and therefore catalyze a rice green revolution in sub-Saharan Africa (Matsumoto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between spikelet fertility and panicle number should be an important consideration while progressing crop improvement for cold tolerance involving WAB56-104 and its descendants such as the NERICAs. We have previously observed such a relationship to contribute to relatively high grain weights per plant under cold stress in NERICA 3 and 4 due to production of few panicles with high number of spikelets per panicle coupled with relatively high filled grain ratio (Wainaina et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Low temperatures, especially during panicle development and the booting stage, decrease the spikelet fertility of rice (Gunawardena et al, 2003;Shimono et al, 2002), resulting in considerable grain yield losses. In our previous study, we reported the suitability of NERICA 1 and NERICA 2 for production in the cold-prone regions of East Africa (Wainaina et al, 2015). Furthermore, we found out that WAB56-104 (O. sativa parent of NERICA1 to NERICA11) has greater cold tolerance based on spikelet fertility than the NERICAs and serves as a good genetic resource for breeding and improvement of cold tolerance of rice cultivars (Wainaina et al, 2015).…”
Section: Agronomic Traits Measurementsmentioning
confidence: 93%
See 1 more Smart Citation